Active Vibration Control of Rectangular Plate with Piezoceramic Elements - BATKO, Wojciech; KOZUPA, Michał (Archives of Acoustics, 2008)
This paper represents the possibilities of reducing mechanical vibration of plates by active vibration control through piezoceramic elements placed on the plane. In the preliminary research a rectangular plate made of aluminium was analyzed. Sound insulation and vibrations measurement were executed on a specialized enclosure in reverberation chamber. A PZT piezoceramic was proposed to control vibrations of the plate. Piezoelements were located in four points on the plate, which have maximum amplitude for (2,2) mode. Vibrations and transmitted sound before and after control is compared using sound and vibration analyser. The results show that after control, vibrations are reduced 10 dB